A Rare Case of Tacharhytmia Presenting with Cardiomyopathy: Permanent Junctional Reciprocating Tachycardia - Nihal Akçay; Osman Yeşilbaş; Hasan Serdar Kıhtır; Mehmet Bedir Akyol; Mey Talip Petmezci; Ülkem Koçoğlu Barlas; Esra Şevketoğlu (Galenos Yayinevi, 2017)
Permanent junctional reciprocating tachycardia is a rare type of supraventricular tachycardia. Incessant tachycardia may result in dilated cardiomyopathy and the patients may have a diagnosis of idiopathic dilated cardiomyopathy. A 53-day-old female infant was brought to the hospital with sweating, rapid breathing, and rapid heartbeat. She was admitted to the intensive care unit with a suspicion of myocarditis. Electrocardiography showed a heart rate of 220/min consistent with narrow QRS complex tachycardia and negative p waves in inferior leads (II, III, and aVF). Medical treatment provided control of the tachycardia episode. In this report, we conclude that patients with a diagnosis of dilated cardiomyopathy should be thoroughly investigated in terms of reversible arrhythmia causes.